A Cross-Platform Mobile Attendance System Utilizing Geofencing and Multi-Factor Authentication - Wisdom Korkortsi; Edmund Dasori Azundow; Ramatu Al-Hassan; Yaw Amankrah Sam-Okyere; Mohammed Izzu-deen Zakariah (MSD Institute, 2026)
The challenge of accurately managing student attendance in higher education persists due to the limitations of manual methods, such as susceptibility to fraud and inefficiency amid growing enrollments. This paper introduces a cross-platform mobile attendance system developed using the Flutter framework and Google Firebase backend, incorporating geofencing and device-binding multi-factor authentication to ensure secure,